DEVELOPING ENGLISH MATERIALS BASED ON CHARACTER BUILDING FOR MANAGEMENT CLASS IN STIE CENDEKIA - Hafidza Nash’ul Amrina; Latifah Anom (Universitas Pendidikan Mandalika, 2019)
Nowadays character building is a national movement in Indonesia. The educators are asked to integrate it in the learning process, but unfortunately, there are still many lectures that still have difficul in integrating character building in classroom. In English class character building can be integrated through inserting culture in the material, therefore the students are not only learning about the material but they also learn about the value of the culture. The purpose of this research is to develop English material for management class based on character building. Research and Development (R&D) by Borg and Gall (1983) was applied. The subjects of the research were the English lecture of management class and the students of the fourth semester. The result of the research showed that the instructional materials developed is appropriate to the students’ needs and curriculum.